Karakterisasi dan Pengembangan Metode Analisis Kromatografi Cair Kinerja Tinggi (KCKT) untuk Penetapan Kadar Asam Glikolat sebagai Calon Baku Pembanding - Dila kartika Aprianti; Neni Isnaeni (Journal of Chemistry Sciences and Education, 2026)
Glycolic acid is a widely used peeling agent in skincare cosmetics that is effective in treating hyperpigmentation, wrinkles, and acne scars. However, due to its potential to cause irritation and erythema, the concentration of this substance in cosmetic products must be strictly controlled. This study aimed to develop an analytical method and to establish a reference value for glycolic acid in order to enhance laboratory testing capabilities for the regulatory surveillance of cosmetic products in the community. Raw material characterization was carried out using infrared spectrophotometry and High-Performance Liquid Chromatography (HPLC). Purity testing was performed using Differential Scanning Calorimetry (DSC) and HPLC, while water content was determined by coulometric analysis. Homogeneity testing and assignment of the content (assigned value) were conducted using an HPLC–PDA system equipped with an autosampler and a C18 column (250 × 4.6 mm i.d., 5 µm). The mobile phase consisted of 15% methanol (pH 2 adjusted with 85% orthophosphoric acid). The results showed that the raw material purity determined by DSC was 98.06% with a melting point of 74.15 °C, while HPLC purity testing detected a total impurity level of 0.40%. The water content of the raw material was recorded at 0.62%. Statistical analysis confirmed that the material was homogeneous, as indicated by an F calculated value lower than the F table value (1.97 < 3.02). Using this method, the assigned value of glycolic acid content was determined to be 98.98% with an associated uncertainty (U) of 1.54%. All validation parameters of the developed analytical method met the acceptance criteria, demonstrating that the HPLC–PDA method is accurate and valid for the determination of glycolic acid content. Based on the purity profile, homogeneity, and assigned value obtained, this raw material is legitimate and suitable for use as a glycolic acid reference standard in cosmetic testing.